Intervenções obstétricas durante o trabalho de parto e parto em mulheres de risco habitual de uma Maternidade de referência do Ceará - Medeiros, Maxsuênia Queiroz (2016)
Obstetric care has become surrounded by unnecessary and invasive procedures in an attempt to minimize the deleterious effects the World Health Organization in 1996 categorized the delivery and birth care practices: demonstrably useful and should be encouraged (Category A) clearly harmful or ineffective and should be eliminated (Category B), practices that do not have evidence to support their recommendation (Category C) and which are often used in inadequate way (Category D). This study aims to characterize the obstetric care during labor and delivery in normal-risk women in the Maternity School Assis Chateaubriand - UFC. cross-sectional study, carried out between April 2014 and January 2015, with 421 mothers of normal risk, admitted in spontaneous or induced labor with a live fetus at admission and single pregnancy, term, with fetuses weighing between 2,500 and 4,499 g. The data collection instrument was divided into blocks with sociodemographic and clinical characteristics, obstetric care during labor, delivery and birth, maternal morbidity, maternal outcome and obstetric practices in Category A and Category B executed and perinatal outcomes. The values ​​are presented as mean ± standard deviation. The chi-square test was used to examine associations between groups. To compare continuous variables we used the Student t test and the Student t test for unpaired scalar variables or Mann-Whitney test. It is considered statistically significant a value of p <0.05. The study was approved by the Ethics Committee under number 957 050. Obstetric practices category most prevalent were oxytocin in the third stage (97.1%), partograph (95%), non-invasive methods for pain relief (87.2) and an accompanying person (84.6%). While the most prevalent category B were more than a vaginal ring over 2 hours (50.4%) and intravenous infusion (44.9%) and oxytocin on the first and second stage of labor (28%) patients. The "best practices" were more prevalent in women of vaginal birth via caesarean sections eventually become more prone to coursing with obstetrical interventions in category B. Among the normal delivery and cesarean groups maternal results show little significant difference except for infection puerperal which was more prevalent in the abdominal delivery group among newborns the worst outcomes (resuscitation in SP, oxygen, ICU and Apgar score below 7 in the first minute) were more frequent in the group that was born by cesarean section.